A girl like him [videorecording (DVD)] - Murisier, Lena; Weber, Amy; Feldshuh, Tovah; Orsini, Kate, 1967-; Howard, John-Paul (Cineverse, 2025)
A Girl Like Him is a coming of age drama centered around a small-town teen who makes a surprising life change, spiraling their lifelong best friend into a dark place when he realizes things will never be the same between them.